The impact of a high-protein diet with strength training on the gastrointestinal microbiota in community-dwelling older adults: subanalysis of a randomized controlled trial - Zöhrer, Patrick A.; Unterberger, Sandra; Aschauer, Rudolf; Draxler, Agnes; Somloi, Sophie; Kapeller, Maria; Bauer, Teresa; Heinz, Cornelia; Reichstam, Stefanie; Franzke, Bernhard; Strasser, Eva-Maria; Hausmann, Bela; et al. (Frontiers in Nutrition, 2026)
BackgroundA balanced gastrointestinal (GI) microbiota is essential for healthy aging. Although high-protein diets and strength training are recommended for older adults to maintain muscle mass, their effects on GI microbiota remain unclear.MethodsThis randomized controlled trial examined the effect of a habitual diet with recommended protein intake or high protein intake combined with strength training on the GI microbiota of 112 community-dwelling adults aged 65–85 years. The participants were divided into three groups: no intervention control (CON), recommended protein intake plus strength training (RP + T), and high protein intake plus strength training (HP + T). Over 17 weeks, protein intake increased significantly from 0.80 (IQR: 0.30–0.50) g/kg body weight at baseline, reaching 1.07 ± 0.25 g/kg in RP + T, and 1.62 ± 0.37 g/kg in HP + T groups. Stool samples collected at baseline, after dietary intervention, and after combined dietary and training intervention were analyzed using 16S rRNA gene amplicon sequencing.ResultsDespite increased protein intake, microbiota richness, diversity, and composition showed no significant changes within or between groups. Residual energy and inflammatory markers indicated that higher protein intake was well tolerated.ConclusionThe findings suggest that increasing protein intake via food sources up to 1.6 g/kg body weight for more than 4 months, with or without strength training, does not adversely affect the GI microbiota composition in older adults.